The Morphology Character of Japanese Taro (Colocasia esculenta var. Antiquorum) In Induction of Polyploidization Mutations In Vitro: A Case Study of Increased Concentration and Duration of Immersion of Colchicine Mutagens - Sudirman Sudirman; Nirwansyah Amier; Ihsan Syawal Rahmat (International Journal of Applied Biology, 2022)
Japanese taro is an alternative food commodity and has prospects as an export commodity, especially to Japan. Colchicine is a mutagen that can be used in polyploid mutations but can be toxic in plants. The purpose of this study was to determine the effect of various concentrations of colchicine and immersion time on the growth and morphological characters of Japanese taro plantlets in vitro. In this study, there were 2 focus factors of treatment. The first factor is colchicine concentration consisting of 0.0% (K0/control), 0.1% (K1), 0.2% (K2) and 0.3% (K3). the second factor is the immersion time consisting of 48 hours (T1), 72 hours (T2) and 96 hours (T3). The treatment of in vitro shoot immersion with 0.1%, 0.2% and 0.3% concentration of colchicine solution for 48 hours, 72 hours and 96 hours was significantly different from the control. Explant growth decreased every week and died at 6 MSI on colchicine treatment. The level of concentration and duration of immersion with different colchicine caused different color changes of the explants, the higher the concentration of colchicine and the duration of immersion, the color of the explants would quickly turn brown.